+0  
 
0
66
1
avatar

Three points are on the same line if the slope of the line through the first two points is the same as the slope of the line through the second two points. For what value of c are the three points (2,4), (6,3), and (-5,c) on the same line?

Guest Aug 16, 2017
edited by Guest  Aug 16, 2017

Best Answer 

 #1
avatar+1828 
0

To solve this problem, first find the slope of the first two points.

 

\(m=\frac{{y}_{2}-{y}_{1}}{{x}_{2}-{x}_{1}}\)

 

\(m=slope\)

 

\({y}_{2}=\)y-point in second point

 

\({y}_{1}=\)y-point in first point

 

\({x}_{2}=\)x-point in second point

 

\({x}_{1}=\)x-point in first point

 

\({y}_{2}=3\)

 

\({y}_{1}=4\)

 

\({x}_{2}=6\)

 

\({x}_{1}=2\)

 

\(m=\frac{3-4}{6-2}\)

 

\(m=\frac{-1}{6-2}\)

 

\(m=\frac{-1}{4}\)

 

\(m=-\frac{1}{4}\)

 

Next, do the same for the second and third points and solve for c.

 

\(m=-\frac{1}{4}\)

 

\({y}_{2}=c\)

 

\({y}_{1}=3\)

 

\({x}_{2}=-5\)

 

\({x}_{1}=6\)

 

\(-\frac{1}{4}=\frac{c-3}{-5-6}\)

 

\(-\frac{1}{4}=\frac{c-3}{-11}\)

 

\(-\frac{1}{4}\times-11=\frac{c-3}{-11}\times-11\)

 

\(\frac{11}{4}=\frac{c-3}{-11}\times-11\)

 

\(\frac{11}{4}=c-3\)

 

\(\frac{11}{4}+3=c-3+3\)

 

\(\frac{11}{4}+\frac{12}{4}=c-3+3\)

 

\(\frac{11+12}{4}=c-3+3\)

 

\(\frac{23}{4}=c-3+3\)

 

\(5.75=c-3+3\)

 

\(5.75=c-0\)

 

\(5.75=c\)

 

\(c=5.75\)

gibsonj338  Aug 16, 2017
edited by gibsonj338  Aug 16, 2017
Sort: 

1+0 Answers

 #1
avatar+1828 
0
Best Answer

To solve this problem, first find the slope of the first two points.

 

\(m=\frac{{y}_{2}-{y}_{1}}{{x}_{2}-{x}_{1}}\)

 

\(m=slope\)

 

\({y}_{2}=\)y-point in second point

 

\({y}_{1}=\)y-point in first point

 

\({x}_{2}=\)x-point in second point

 

\({x}_{1}=\)x-point in first point

 

\({y}_{2}=3\)

 

\({y}_{1}=4\)

 

\({x}_{2}=6\)

 

\({x}_{1}=2\)

 

\(m=\frac{3-4}{6-2}\)

 

\(m=\frac{-1}{6-2}\)

 

\(m=\frac{-1}{4}\)

 

\(m=-\frac{1}{4}\)

 

Next, do the same for the second and third points and solve for c.

 

\(m=-\frac{1}{4}\)

 

\({y}_{2}=c\)

 

\({y}_{1}=3\)

 

\({x}_{2}=-5\)

 

\({x}_{1}=6\)

 

\(-\frac{1}{4}=\frac{c-3}{-5-6}\)

 

\(-\frac{1}{4}=\frac{c-3}{-11}\)

 

\(-\frac{1}{4}\times-11=\frac{c-3}{-11}\times-11\)

 

\(\frac{11}{4}=\frac{c-3}{-11}\times-11\)

 

\(\frac{11}{4}=c-3\)

 

\(\frac{11}{4}+3=c-3+3\)

 

\(\frac{11}{4}+\frac{12}{4}=c-3+3\)

 

\(\frac{11+12}{4}=c-3+3\)

 

\(\frac{23}{4}=c-3+3\)

 

\(5.75=c-3+3\)

 

\(5.75=c-0\)

 

\(5.75=c\)

 

\(c=5.75\)

gibsonj338  Aug 16, 2017
edited by gibsonj338  Aug 16, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details